PEMBERIAN LIMBAH CAIR PABRIK KELAPA SAWIT (LCPKS) DAN NPK TABLET TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI TANAH GAMBUT PADA PEMBIBITAN UTAMA - Sholeh, Khairul; Amri, Al Ikhsan; ', Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research was to determine the effect of giving LCPKS and NPK Tablet, and single factor LCPKS and NPK Tablet and get the best dose giving on the growth of oil palm seedling at main nursery. This research was conducted at the experimental station of Agriculture Faculty, University of Riau on March 2015 until June 2015. This research was arranged on using Completely Rendomized Design (CDR) with two factorial: Factor I; Application Of Palm Oil Liquid Of Waste, L0 (without LCPKS), L1 (LCPKS 600 ml),L2 (LCPKS 1200 ml),L3(LCPKS 1800 ml). Factor II; N0(without NPK Tablet), N1 (2 tablet NPK), N2 (4 tablet NPK) and replicated 3 times, so abtained 72 unit experiment. Parameter observed were the accretion of plant heigh, accretion of stump diameter, accretion of leaves number, root volume, root shoot ratio and dry weight.The result showed that giving LCPKS and NPK Tablet increase accretion of stum diameter, accretion of leaves number and dry root with get the best dose 1800 ml and 2 tablet NPK. Giving LCPKSincrease accretion of  plant heigh, accretion of stump diameter, accretion of leaves number, root volume, root shoot ratio and dry weight with dose 1800 ml. Giving NPK Tablet the increase accretion of plant heigh, theaccretion of stump diameter,theaccretion of leaves, numberroot shoot ratio and dry weight with get the best dose 2 tablet. Keywords : Oil palm seedling, LCPKS, NPK Tablet,peat soil